A study on the mechanism of the impact of entrepreneurship opportunity collaboration on opportunity innovation: The mediating effect of resource patchwork - Chen, Bo (Nurture, 2024)
Purpose: This article explores the impact of opportunity collaboration on opportunity innovation based on the identification, acquisition, sharing and exchange of resources and elements among entrepreneurial entities through collaborative and interactive behaviors to explore the influence mechanism of entrepreneurial opportunity collaboration on the formation of innovativeness of opportunities and the mediating role of resource patchwork. Design/Methodology/Approach: The research conducted an empirical analysis on the impact of opportunity collaboration on opportunity innovation based on the data of 207 entrepreneurial enterprises from Beijing, Guangdong and Henan with a high entrepreneurial vitality index and vital data availability. Resource patchwork's mediation effect is discussed and empirically tested from the patchwork theory perspective. Findings: Entrepreneurial opportunity collaboration significantly positively affects opportunity innovation and resource patchwork plays an intermediary role between them. Conclusion: Innovation is an important attribute to distinguish the heterogeneity of entrepreneurial opportunities and is also the key to entrepreneurial success. Interaction among various entrepreneurial elements should be strengthened to achieve efficient and high-quality resource patchwork to obtain a significant "synergistic effect" and ultimately improve innovation in entrepreneurial opportunities. Practical Implications: This study not only helps to theoretically understand the impact of entrepreneurial opportunity collaboration on opportunity innovation differentiation but also has outstanding practical reference significance for the government's targeted policy measures to support innovative entrepreneurial activities and for entrepreneurs to identify or create innovative opportunities.